The spirit of the disciplines : understanding how God changes lives - Willard, Dallas, 1935-2013. (San Francisco : HarperSanFrancisco, 1990)
Dallas Willard, one of today's most brilliant Christian thinkers and author of The Divine Conspiracy, presents a way of living that enables ordinary men and women to enjoy the fruit of the Christian life. He reveals how the key to self-transformation resides in the practice of the spiritual disciplines, and how their practice affirms human life to the fullest. The Spirit of the Disciplines is for everyone who strives to be a disciple of Jesus in thought and action as well as intention.
Includes bibliographical references (pages 266-270) and indexes.
Keywords: Spiritual life -- Christianity; Spiritual life -- Christianity